Mechanical Characteristics of Cylinder Pin Tumbler Locks as They Relate to Resistance Testing - Boros, Martin; Siser, Anton; Kekovic, Zoran; Mazal, Jan (Communications - Scientific letters of the University of Zilina, 2018)
In recent years, there has been a great development of methodologies, procedures and software tools for quantitative assessment of reliability, efficiency and effectiveness of physical protection systems. Absence of some important input values, as well as missing method to obtain them, is still the most serious problem. This paper is focused on analysis of possibilities how to obtain delay time values in the case of cylinder pin tumbler locks using non-destructive methods of breaking. In the introduction of the article, a proposal of the methodology for testing the mechanical resistance of cylinder pin tumbler locks is elaborated. Consequently, the focus is set on analysis of results obtained during the pilot tests in order to verify the correctness of the proposed methodology. With the tests, it is possible to assess the resulting resistance of cylinder pin tumbler locks also in terms of classification into resistance classes. The pilot testing needs to be implemented mainly due to the lack of a technical standard that processes the issue within the established methodology.